Evidentiality in Darma (Tibeto-Burman) - Willis, Christina M. (2024)
This paper outlines the evidentiality system found in Darma, a Tibeto-Burman language spoken in Uttarakhand, India. The source of information is indicated for four levels: direct evidence, general knowledge, inferential and reported. Sources that come from direct evidence and general knowledge are indicated through the choice of verb. The former is indicated with an equational verb and the latter is indicated with an existential verb. Information that is inferred is indicated in two possible ways. Either a bare verb stem is followed by a grammaticalised form of the existential, or a future form of the verb is followed with the grammaticalised form of the existential. The reported evidential is a clause final particle that is grammaticalised from the lexical verb ‘to say/call’. Indicating information source is not obligatory in Darma. The examples illustrating evidentiality in Darma are from a corpus of natural discourse.